Intrinsically Disordered Proteins: Mechanics, Assemblies, and Structural Transitions - Bagheri, Mehran (Université d'Ottawa / University of Ottawa, 2017)
Proteins are essential parts of living organisms that initiate and control almost all cellular processes. Despite the widely accepted belief that all functional proteins fold into stable and well-defined three-dimensional (3D) structures mandatory for protein activity, the existence of biologically functional disordered proteins has been increasingly recognized during past two decades. Proteins with inherent structural disorder, commonly known as intrinsically disordered proteins (IDPs), play many roles in a biological context. However, in contrast to their folded counterparts, they are dynamically unstructured and typically fluctuate among many conformations even while performing biological functions. In fact, it is this dynamical structural heterogeneity that that allows for IDPs to interact with other biological macromolecules in unique ways. Moreover, while a majority of proteins in eukaryotic proteomes have been found to have intrinsically disordered regions (IDR), the mechanisms by which protein disorder fives rise to biological functionality is still not well understood. Through a series of simulation studies on specific systems, this thesis probes several aspects of the emerging structure-function paradygm of IDPs, namely the mechanics, intermolecular assembly, and structural transitions occurring in these proteins. The lack of well-defined 3D structure in IDPs gives rise to distinct mechanical properties, the subject of the first study in the thesis on the elasticity of a elastomeric gluten-mimetic polypeptide with an intrinsically disordered character. This disordered polypeptide was shown to exhibit distinctively variable elastic response to a wide range of tensions, which a classical worm-like chain model failed to accurately describe, thus requiring a molecular-level analysis. IDPs frequently are frequently involved in protein-protein interactions, the focus of the second study on the propensity of an IDR, the B domain in dynamin-related protein 1 (Dpr1), to self-assemble into dimer structures while remaining disordered in all solution conditions. Despite a hypothesized auto-inhibitory role for this domain in Dpr1 that was assumed to be triggered by an disordered-to-order transition, the B domains in solution showed no tendency to form ordered structures even in the presence of order promoting osmolytes. Instead, self-association in the presence of osmolyte was found to occur by favorable intermolecular intereactions between specific region on the surface of the B-domains. Other IDPs do undergo a disorder-to-order transition in response to environmental cues, in ways that are unique disordered proteins, the focus of the last study on intermolecular ordering transitions in silk-like proteins. Factors such as protein sequence and physical tension were investigated, and results suggested that tyrosine residues in the key silk sequence motifs promote templating of beta structure from disordered precursors and that elongational stresses preferentialy stabilize antiparallel beta-sheet order. Together, these three computational studies provide insight into the nature of the structure-function mechanisms of IDPs.
Keywords: Silk; Drp1; Gluten protein; Dynamin related protein; Elasticity; Worm-like chain model; IDPs; Intrinsically diordered protein; Self assemblie; Tyrosine crosslinking